The Mediating Role of Digital Financial Inclusion in the Effects of Perception of KUR and Islamic Financial Behavior on MSME Capital Decisions - Nita Fauziah Oktaviani; Evilia Sri Yuniar (MIX: JURNAL ILMIAH MANAJEMEN, 2026)
Objectives: This study aims to examine how MSME owners’ perceptions of the People’s Business Credit (KUR) program and their Islamic financial behavior influence capital decision-making. Specifically, it evaluates both the direct effects of KUR perceptions and Islamic financial behavior on capital decisions and the indirect effects operating through digital financial inclusion, which is expected to function as a bridging mechanism by improving access to information and digital financial services. By clarifying these pathways, the study also seeks to provide evidence that can support government stakeholders and MSME owners in strengthening digital financial inclusion initiatives that facilitate better informed and more effective capital decisions.Methodology: The subject of this study is the owner of MSMEs in East Priangan Region Indonesia consisting of 7 regencies/cities with a sample count of 250 MSME, as for data collection using purposive sampling technique. The analysis tool used is SEM-PLS Ver 4.Finding: The results indicate that KUR perceptions have a significant direct effect on capital decisions, whereas Islamic financial behavior does not significantly influence capital decisions directly. Digital financial inclusion significantly mediates the effects of both KUR perceptions and Islamic financial behavior on capital decisions.Conclusion: These findings suggest that digital financial inclusion plays a central role in translating program perceptions and financial behavior into capital decision-making among MSMEs. Strengthening an inclusive and equitable digital finance ecosystem may help MSME owners improve their knowledge and access to financial services, thereby supporting better capital allocation decisions.